Anticipatory responses of catecholamines on muscle force production - French, Duncan N; Kraemer, William J; Volek, Jeff S; Spiering, Barry A; Judelson, Daniel A; Hoffman, Jay R; Maresh, Carl M (Journal of applied physiology (1985), 2007)
1 Human Performance Laboratory, Department of Kinesiology, University of Connecticut, Storrs, Connecticut; and 2 Department of Health and Exercise Science, The College of New Jersey, Ewing, New Jersey Submitted 22 May 2006 ; accepted in final form 28 August 2006 Few data exist on the temporal relationship between catecholamines and muscle force production in vivo. The purpose of this study was to examine the influence of preexercise arousal on sympathoadrenal neurohormones on muscular force expression during resistance exercise. Ten resistance-trained men completed two experimental conditions separated by 7 days: 1 ) acute heavy resistance exercise protocol (AHREP; 6 x 10 repetitions parallel squats, 80% 1 repetition maximum) and 2 ) control (Cont; rest). Peak force (F peak ) was recorded during a maximal isometric squat preceding each set and mean force (F mean ) was measured during each set. Serial venous blood samples were collected before the AHREP and immediately preceding each set. Blood collection times were matched during Cont. Preexercise epinephrine (Epi), norepinephrine (NE), and dopamine (DA) increased ( P 0.05) above Cont by 270, 255, and 164%, respectively. During exercise, Epi, NE, and DA continued to increase by 512, 271, and 38%, respectively, above preexercise values. F peak and F mean decreased by 2025% over the course of the AHREP. Post hoc data analysis revealed that five subjects (F maintainers ) showed no decline ( P 0.05) in muscular performance (F peak , F mean ) during AHREP and that five subjects (F reducers ) had significant reductions in F peak and F mean . Integrated area under the curve for Epi, NE, and F peak were greater ( P < 0.02) for F maintainers than F reducers . In conclusion, an anticipatory rise in catecholamines existed, which may be essential for optimal force production at the onset of exercise. epinephrine; norepinephrine; dopamine; strength; resistance exercise Address for reprint requests and other correspondence: W. J. Kraemer, Human Performance Laboratory, Dept. of Kinesiology, Unit 1110, Univ. of Connecticut, Storrs, CT 06269-1110 (e-mail: William.Kraemeratuconn.edu )